Epilithic algae of Çalgan creek - Caglar, M.; Coskun, E.; Selamoglu, Z. (Green Wave Publishing of Canada, 2020)
In this study, the epilithic algae in the samples collected from three stations on the Çalgan Creek (Elazığ) in Fırat University between January and June 2016 were investigated in terms of some physical and chemical parameters. During the study, 44 taxa of epilithic algae were recorded. It was observed that Euglenophyta (1 species), Cyanophyta (3 species), Chlorophyta (6 species) and Bacillariophyta (34 species) both had the most species and were the most important algae in the epilithic algal community considering their frequency of occurrence and population size. © 2020, Green Wave Publishing of Canada. All rights reserved.
Keywords: Algae; Elazığ; Epilithic; Çalgan Creek